2019
DOI: 10.1016/j.cgh.2019.03.042
|View full text |Cite
|
Sign up to set email alerts
|

Smaller-Diameter Covered Transjugular Intrahepatic Portosystemic Shunt Stents Are Associated With Increased Survival

Abstract: BACKGROUND & AIMS: We studied the effects of diameter of covered, self-expandable, nitinol stents on survival times of patients with a transjugular intrahepatic portosystemic shunt (TIPS). METHODS: We collected data from 185 patients (median age, 55 y; 30% female) who received a covered nitinol stent, from February 2006 through September 2010, using the online multicenter German TIPS registry. TIPS were given to 107 patients for refractory ascites and to 78 patients for variceal bleeding. Patients at risk of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
1
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 22 publications
2
84
1
2
Order By: Relevance
“…34,35 Growing evidence has been published that suggests less complications after TIPS by using smaller diameter stents or dilatation of stents smaller than the nominal diameter, suggesting a beneficial effect of less shunt volume. [36][37][38][39][40] Regarding other decompensating events, we were unable to find a significant difference in variceal bleeding, hepatorenal syndrome or spontaneous bacterial peritonitis between patients with L-TSA and S-TSA. Considering variceal bleeding, our data are supported by previous reports, in which only the presence of SPSS vs. no SPSS was shown to be associated with bleeding, but no differences between small and large SPSS were detected.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…34,35 Growing evidence has been published that suggests less complications after TIPS by using smaller diameter stents or dilatation of stents smaller than the nominal diameter, suggesting a beneficial effect of less shunt volume. [36][37][38][39][40] Regarding other decompensating events, we were unable to find a significant difference in variceal bleeding, hepatorenal syndrome or spontaneous bacterial peritonitis between patients with L-TSA and S-TSA. Considering variceal bleeding, our data are supported by previous reports, in which only the presence of SPSS vs. no SPSS was shown to be associated with bleeding, but no differences between small and large SPSS were detected.…”
Section: Discussionmentioning
confidence: 55%
“…In non-spontaneous SPSS, such as TIPS, it has been previously shown that small diameter TIPS-shunts are associated with less hepatic encephalopathy and better survival than the commonly used 10 mm stents. 37,38,40 However, in case of TIPS, the collaterals and the A B Research Article other SPSS have been rigorously embolized in order to limit TSA to 10 mm and other persisting collaterals (in many patients present) may have contributed to non-significant results regarding survival. This study presents a large, multicentric, international, well characterized cohort of cirrhotic patients with SPSS.…”
Section: Discussionmentioning
confidence: 99%
“…108 of the identified papers were abandoned with the preset inclusion and exclusion criteria. Five studies including 2 RCTs [ 13 , 16 ] and 3 retrospective cohort studies [ 15 , 20 , 21 ] from 2010 to 2019 were included into the meta-analysis. Figure 1 provides the flow diagram of publication retrieval, screening, and resulting study selection.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 provides the flow diagram of publication retrieval, screening, and resulting study selection. Data from Trebicka et al [ 20 ] was retrieved based on a multicenter RCT and propensity score matching for known confounders, so this study was categorized as having an observational feature [ 20 ]. The total number of patients reported in the five studies was 489.…”
Section: Resultsmentioning
confidence: 99%
“…Aber welches Vorgehen ist dafür geeignet? Soll man sich auf den "optimalen" PSG von 12 mmHg verlassen [15], oder ist der Stentdurchmesser von 8 mm [23,24] das richtige Maß? Da ist es besonders wichtig, die individuellen Risiken klar abzuschätzen und danach den optimalen Stentdurchmesser (6-10 mm) einzustellen (▶ Abb.…”
Section: Präoperativer Tipsunclassified